2016
DOI: 10.1002/jcb.25483
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone‐Induced Skeletal Muscle Atrophy Increases O‐GlcNAcylation in C2C12 Cells

Abstract: Skeletal muscle atrophy is a well-known adverse effect of chronic treatment with glucocorticoids and it also occurs when stress conditions such as sepsis and cachexia increase the release of endogenous glucocorticoids. Although the mechanisms of action of these hormones have been elucidated, the possible molecular mechanisms causing atrophy are not yet fully understood. The involvement of the O-GlcNAcylation process has recently been reported in disuse atrophy. O-GlcNAcylation, a regulatory post-translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
4
21
0
1
Order By: Relevance
“…Skeletal muscle atrophy is an established adverse effect caused by treatment with glucocorticoids. 62 Consistently, we also observed reduced mRNA levels of Pak1 in atrophying myotubes following dexamethasone exposure in vitro (Figure 2E). Dexamethasone treatment causes myotube atrophy, as seen by reduced protein synthesis ( Figure S6A), while at the same time induces a down-regulation of Pak1 expression and MuRF1 induction (Figure 2E and 2F).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Skeletal muscle atrophy is an established adverse effect caused by treatment with glucocorticoids. 62 Consistently, we also observed reduced mRNA levels of Pak1 in atrophying myotubes following dexamethasone exposure in vitro (Figure 2E). Dexamethasone treatment causes myotube atrophy, as seen by reduced protein synthesis ( Figure S6A), while at the same time induces a down-regulation of Pak1 expression and MuRF1 induction (Figure 2E and 2F).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, CSA analysis of TA from C26‐bearing mice previously electroporated with DsRed2‐PAK1 or DsRed2 expressing plasmids suggested that overexpressed Pak1 preserves fiber area during cancer‐induced muscle wasting (Figure D–F). Skeletal muscle atrophy is an established adverse effect caused by treatment with glucocorticoids . Consistently, we also observed reduced mRNA levels of Pak1 in atrophying myotubes following dexamethasone exposure in vitro (Figure E).…”
Section: Resultsmentioning
confidence: 93%
“…In the present study, Dex was used as a muscle atrophy inducer. It has been used for inducing muscle atrophy in 2D cultured skeletal muscle cells in vitro [ 8 , 23 , 24 ]. Dex treatment induced the expression of skeletal muscle atrophy-related genes, Atrogin-1 and MuRF-1 , in myotubes and decreased the size of myotubes and the amount of muscle protein.…”
Section: Introductionmentioning
confidence: 99%
“…In initial experiments we exposed the C2C12 myotubes to 10 µM Dexa (defined as a 'mild Dexa treatment') and, as recently published, this treatment caused a decrease in MyHC protein levels in scrambled siRNA-treated control cells (Fig. 8A) (Massaccesi et al, 2016). In cells impeded for the expression of either MuRF1 or DCAF8 the loss of MyHC was less pronounced.…”
Section: Dcaf8 Is Required For Myhc Degradationmentioning
confidence: 78%
“…To this end, we differentiated C2C12 cells that were downregulated for expression of individual genes into myotubes and induced atrophy using the glucocorticoid dexamethasone (Dexa). Dexa treatment serves as an established method to investigate muscle atrophy in cell culture but widely different concentrations of this substance have been used in individual studies (Hasselgren, 1999;Clarke et al, 2007;Menconi et al, 2008;Massaccesi et al, 2016). In initial experiments we exposed the C2C12 myotubes to 10 µM Dexa (defined as a 'mild Dexa treatment') and, as recently published, this treatment caused a decrease in MyHC protein levels in scrambled siRNA-treated control cells (Fig.…”
Section: Dcaf8 Is Required For Myhc Degradationmentioning
confidence: 97%